Regulating Investor Protection under EU Law The Unbridgeable Gaps with the U.S. and the Way Forward - Marcacci, Antonio (Springer International Publishing, 2018)
This book analyzes the legal system for the protection of retail investors under the European Union law of investment services. It identifies the regulatory leitmotiv driving the EU lawmaker and ascertains whether and to what extent such a system is self-sufficient, using a set of EU-made and EU-enforced rules that is essentially different and autonomous from the domestic legal orders. In this regard, the book takes a double perspective: comparative and intra-firm. Given the federal dimension of the US legal system and, thus, the "role-model" it plays vis-à-vis the EU, the book compares the two systems. To fully highlight the existing gaps and measure how self-sufficient the EU system is against its American counterpart, the Union/Federal level as such is analyzed - i.e., detached from the national (in EU terms) and State (in US terms) level. Regulating Investor Protection under EU Law also showcases the unique intra-firm perspective from a European investment firm and analyzes how EU-produced public-law rules become a set of compliance requirements for investment services providers. This "within-the-firm" angle gauges the self-sufficiency of the EU system of retail investor protection from the standpoint of an EU-regulated entity. The book is intended for both compliance professionals and academic scholars interested in this topic while also including illustrative sections intended to provide a broader regulatory view for less-experienced readers.